Suggested activities in geometry using manipulative materials for socially-alienated children (grade four) - Fuentes, Maria B.; Adorio, Mercedes P. (1973)
The purpose of this paper was to present the use of manipulative aids in teaching geometrical concepts to the socially-alienated grade four children. The study took geometry as a unit of study to illustrate the feasibility and impact of these materials to children's learning. The problem set forth by this paper was approached through integrative research.
"April, 1973."
Thesis (Master of Arts in Teaching - Special Education : Behavior Problem)--University of the Philippines, Diliman.
Keywords: Geometry -- Study and teaching (Elementary) -- Activity programs -- Philippines; Manipulatives (Education) -- Philippines; Children with social disabilities -- Education (Elementary) -- Philippines